A double moral hazard model for inter‐organizational knowledge sharing. Issue 8 (14th July 2021) - Chen, Guo; Li, Baixun
Abstract: In inter‐organizational knowledge sharing, the firms share sensitive organizational knowledge to jointly solve a problem. However, the knowledge sender may conceal knowledge and the knowledge receiver may misappropriate the knowledge received from the sender. We formalize this situation using the double moral hazard framework and develop Stackelberg game models for symmetric and asymmetric information scenarios. First, we analyse the motivation for triggering double moral hazard. We find that by concealing knowledge, the sender cannot reduce the loss due to misappropriating knowledge. Second, we analyse the impact of improved punishment mechanism on the behaviours that trigger double moral hazard, and find that there exists a threshold policy with respect to monitoring effort to prevent double moral hazard. Third, we get the conditions under which the partner has the motivation to prevent the monitor from adopting a deception strategy.